2008
DOI: 10.1128/aac.00211-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Anidulafungin against Candida albicans Biofilms

Abstract: We tested the activity of anidulafungin against 30 Candida albicans isolates. The planktonic MICs for 50 and 90% of the isolates tested (MIC 50 and MIC 90 ) were <0.03 and 0.125 g/ml, respectively (MIC range, <0.03 to 2 g/ml). The sessile MIC 50 and MIC 90 were <0.03 and <0.03 g/ml, respectively (MIC range, <0.03 to >16 g/ml).Candida albicans infections seen in modern clinical practice, such as device-and intravascular catheter-related infections (2, 5), are associated with the growth of organisms in a biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 8 publications
3
17
1
4
Order By: Relevance
“…Similarly to our study, the data of Jacobson et al (2008) showed the SMIC 50 for anidulafungin to be ¡0.03125 mg ml 21 in 28 of 30 C. albicans clinical isolates tested when the biofilm was formed in RPMI 1640 medium. In contrast to the work of Katragkou et al (2008), we did not observe any indication of paradoxical growth during caspofungin activity against a mature C. albicans biofilm, even when high concentrations (4-8 mg ml 21 ) of the drug were administered to biofilms (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to our study, the data of Jacobson et al (2008) showed the SMIC 50 for anidulafungin to be ¡0.03125 mg ml 21 in 28 of 30 C. albicans clinical isolates tested when the biofilm was formed in RPMI 1640 medium. In contrast to the work of Katragkou et al (2008), we did not observe any indication of paradoxical growth during caspofungin activity against a mature C. albicans biofilm, even when high concentrations (4-8 mg ml 21 ) of the drug were administered to biofilms (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Overall, anidulafungin was the most potent agent against C. albicans biofilms; the anidulafungin SMIC was previously determined to be Յ0.03 g/ml for 28/30 isolates (7). However, the remaining two isolates had anidulafungin SMIC values of Ͼ16 g/ml, one having the highest planktonic anidulafungin MIC (2 g/ml) observed (7). The two isolates with anidulafungin SMICs of Ͼ16 g/ml had caspo-fungin SMICs of Յ0.25 g/ml and micafungin SMICs of 0.25 g/ml (7,12).…”
mentioning
confidence: 97%
“…A recent study exploring the early transcriptional responses of mature Candida albicans biofilm exposed to various antifungal agents suggests that enhanced extracellularmatrix or beta-glucan synthesis during biofilm growth (18) might prevent fluconazole and amphotericin B from reaching biofilm cells, thus impairing their cell toxicity and the associated transcriptional responses (27). As echinocandins are noncompetitive inhibitors of beta-glucan synthesis (20), this may explain why the drugs have been shown to be effective against Candida biofilms (4,8,9,11,28). In another study, liposomal formulation of amphotericin B was shown to eradicate C. albicans biofilm in a continuous catheter flow model, whereas fluconazole and caspofungin were less effective (24).…”
mentioning
confidence: 99%